2018
DOI: 10.1038/s41426-018-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Coccidioides posadasii from xerophytic environments in Venezuela reveals risk of naturally acquired coccidioidomycosis infections

Abstract: A wide range of mammals are susceptible to infection by the fungal species Coccidioides immitis and C. posadasii. In humans, 60% of infections are asymptomatic; however, certain patients may develop a severe and deep systemic mycosis called coccidioidomycosis. Genetic analysis suggests that the majority of clinical isolates recovered from South America are C. posadasii; however, little is known about the prevalence, species distribution, and ecological factors that favor the occurrence of this pathogen in thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…Notably, skin test surveys using coccidioidin in Latin American communities revealed positive intradermic test rates of 44% and 46% in the Chaco region of Paraguay and the Lara State of Venezuela, respectively (26, 31). Additionally, environmental molecular detection of Coccidioides posadasii in Venezuela suggests a high prevalence of the organism in the soil (32). The actual occurrence of coccidioidomycosis remains unclear; as fewer than 1,000 total coccidioidomycosis cases have been reported over the last century in South and Central America (19, 26).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, skin test surveys using coccidioidin in Latin American communities revealed positive intradermic test rates of 44% and 46% in the Chaco region of Paraguay and the Lara State of Venezuela, respectively (26, 31). Additionally, environmental molecular detection of Coccidioides posadasii in Venezuela suggests a high prevalence of the organism in the soil (32). The actual occurrence of coccidioidomycosis remains unclear; as fewer than 1,000 total coccidioidomycosis cases have been reported over the last century in South and Central America (19, 26).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies show that coccidioidomycosis in South America is mostly caused by C. posadasii (19, 61, 64). Molecular analyses of soil DNA revealed that Coccidioides is common in xeric environments of Venezuela: all sampled sites (N = 15) were positive for Coccidioides; and sequencing of one of the ribosomal Internal Transcribed Spacers (ITS2) suggested that all the environmental samples from the region are, indeed, C. posadasii (33). Nonetheless, the sample of genotypes was diverse and encompassed multiple ITS2 haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, environmental molecular detection of Coccidioides spp. in Venezuela suggests a high prevalence of C. posadasii in the soil (33). The actual occurrence of coccidioidomycosis remains unclear; as fewer than 1,000 total coccidioidomycosis cases have been reported over the last century in South and Central America (19, 26).…”
Section: Introductionmentioning
confidence: 99%
“…Coccidioidomycosis (Valley Fever) is caused by two epidemiologically and genetically diverse species, C. immitis and C. posadasii [ 34 , 114 120 ]. C. immitis was first discovered in 1892 in Buenos Aires and misidentified as a protozoan; years later, it was correctly identified as a fungus [ 34 , 121 – 124 ].…”
Section: Methodsmentioning
confidence: 99%